Distribution of Integrons and Phylogenetic Groups among Enteropathogenic Escherichia coli Isolates from Children <5 Years of Age in Delhi, India - Singh, Taru; Das, Shukla; Ramachandran, V. G.; Wani, Sayim; Shah, Dheeraj; Maroof, Khan A.; Sharma, Aditi (Frontiers in Microbiology, 2017)
Integrons by means of horizontal gene transfer carry multidrug resistance genes (MDR) among bacteria, including E. coli. The aim of this study was to determine the antibiotic resistance profiles and the genes associated with them, to gain insights in the distribution of phylogroups, prevalence and characterization of class 1, 2 and 3 integrons among Enteropathogenic E. coli (EPEC) isolates, from children upto five years of age from Delhi and National Capital Region (NCR), India. A total of 120 E. coli isolates, including 80 from diarrheagenic E. coli (cases) and 40 from healthy isolates (controls) were recruited in this study. After isolation of E. coli, screening for EPEC was done by conventional multiplex PCR. Antibiotic suseptibility test was performed using disk diffusion method and further confirmed by minimum inhibitory concentration (MICs) by E-test. The presence and characterization of integrons and antimicrobial resistance genes were performed by PCR and DNA sequencing. Phylogeny determination was carried out by quadruplex PCR. EPEC strains were found in 64 of the 80 diarrheagenic cases, out of which 38 were MDR. In the 40 healthy controls, 23 were found to be EPEC strain, out of which only 2 were MDR. Amongst 80 diarrheagenic cases, class 1 integron were observed in 43 isolates, class 2 integron in 12 isolates and 9 isolates were found with co-existence of both. Similarly, in healthy controls; class 1 integron in 9 and class 2 integron in 7 isolates were observed with co-existence in 3 isolates. None of the isolates included class 3 integron. The dfr was the most commonly identified gene cassette within the integron-positive isolates. Phylogenetic studies showed considerable representation of phylogroup B2 in both diarrheagenic cases and healthy controls. This study reiterates the importance of class 1 integron predominantly for acquisition of antibiotic resistance genes among EPEC isolates. Furthermore, it also ascertains the possible association between multidrug resistance and presence of integrons. Approximately 91% of isolates were easily assigned to their respective phylogroups. Assessment of relationship between antibiotic resistance and dominant phylogroups detected was also attempted. This study also highlights the increased burden of antimicrobial resistance in healthy controls.